Does gender really matter in the boardroom? Evidence from closely held family firms (2020)
In this study, using a unique hand-collected sample of 523 closely held Colombian family firms and 5.094 firm-year observations, with 4907 board members, including 833 female board members, we show that female directors have a negative effect on firm performance. However, when we separate female directors into two groups, family female directors and outside female directors, we find that the latter has a positive and significant effect on firm performance. We further construct a human capital index after a detailed analysis of 15% of the total curriculum vitae of directors for those in our sample we were able to find. Although the subsample is not representative enough to make general claims for the whole sample due to data constraints, we shed some light about a potential gender bias in the development of the human capital of heirs and the corresponding impact of different levels of directors’ education and experience on firms’ financial performance.